Agents, environments, scenarios: A framework for examining models and simulations of human-vehicle interaction. (November 2020) - Janssen, Christian P.; Boyle, Linda Ng; Ju, Wendy; Riener, Andreas; Alvarez, Ignacio
Abstract: This paper provides a framework for examining human-vehicle interactions with respect to three dimensions that can involve models or simulations: the agents, the environments, and the scenarios. Agents are considered on a spectrum from human to artificial actors. Environments are considered on a spectrum from simulated to real. Scenarios are considered on a spectrum from constrained to unconstrained. It is argued that these three dimensions capture key differences in research approaches within the field of human-vehicle interaction, and that explicitly situating research and discussions within this framework will allow researchers to better compare and contrast research outcomes and contributions. The framework is used to locate different disciplines in the community with respect to one another, and to identify areas which are as-yet unexplored. Graphical abstract: Unlabelled Image Highlights: Simulations and models can consider three dimensions: agents, environments, and scenarios. Simulation studies do not always simulate all three dimensions. Control (regulation and fidelity) can be applied on each dimension.